Programs for Performing the A Priori Procedure in Skew Normal Contexts - Wang, Cong; Li, Hui; Trafimow, David; Wang, Tonghui; Tong, Tingting (Thailand Statistician, 2025)
Despite being only a few years old, there is already a reasonably large literature on the a priori procedure, designed to aid researchers in determining sample sizes needed to ensure that sample statistics to be obtained provide good estimates of corresponding population parameters. One of the directions this literature has taken has been to expand the typical assumption of normally distributed data to include skew normally distributed data. In turn, the expansion allows the use of locations, or differences in locations; as opposed merely to means, or differences in means. Another direction the expansion has taken is to consider correlation coefficients. However, there is considerable mathematics associated with both expansions that might not be accessible to most substantive researchers. Therefore, the present goal is to provide links to free and user-friendly programs so that even mathematically unsophisticated substantive researchers can perform the calculations.